Pharmacokinetic interaction between taxanes and amiodarone leading to severe toxicity. (20th November 2016) - Hammann, Felix; Gotta, Verena; Conen, Katrin; Medinger, Michael; Cesana, Philipp; Rochlitz, Christoph; Taegtmeyer, Anne B.
Abstract : Adverse event: A drug interaction leading to severe skin and mucosal toxicity. Drugs implicated: Paclitaxel, docetaxel and amiodarone. The patient: A 77‐year‐old woman with a history of hypertension, hyperlipidemia, and palpitations, managed with amiodarone, was treated for HER2‐positive invasive ductal breast cancer with paclitaxel and trastuzumab as an adjunct to surgery. Evidence that links the drug to the event: There was a strong temporal relationship between the taxane therapy and the development of severe skin and mucosal toxicity due to an unexpected reduction in taxane clearance. Management: Initially, conversion of paclitaxel to docetaxel, then cessation of docetaxel, symptomatic treatment, rehydration and placement of a nasogastric tube. Mechanism: Increased exposure to paclitaxel and subsequently docetaxel due to interaction with amiodarone was suspected and confirmed on pharmacokinetic sampling. Analysis of two blood samples taken 9 and 10 days after docetaxel revealed plasma levels of 4.73 and 4.09 ng ml −1, respectively, leading to a 79% decreased individual (Bayesian maximum a posteriori ) clearance estimate of 9.15 l h −1, corresponding to an estimated fivefold increase in AUC. Paclitaxel was also present in these samples (20 and 21 days after the last administration). Implications for therapy: Amiodarone inhibits cytochrome P450 (CYP) isoforms 2C8 and 3A4 as well as P‐glycoprotein (P‐gp) for which taxanes are substrates. However, interactions with amiodarone are not specified in the prescribing information. Clinicians should be aware of this interaction, particularly in an ageing population, where more patients requiring taxanes may already be receiving amiodarone for a comorbid cardiac condition.